Development of E-learning Muhammadiyah (El-Mu) at Mutual Junior High School, Magelang City - Meidar Hadi Avizenna; R. Arri Widyanto; Purwono Hendradi; Mukhtar Hanafi; Nugroho Agung Prabowo; Bambang Pujiarto (Community Empowerment, 2023)
The Covid-19 pandemic which has had an impact on the education sector has forced educators to be more creative and innovative in preparing and implementing digital learning, without face-to-face meetings. Mutual Junior High School teachers already have these potentials, but they are not yet optimal. Some teachers already have digital materials in the form of learning media that use power points and videos. The problem that occurs, the materials owned by the teachers are not structured and there is no standard, even though they refer to the lesson plans. In addition, only a few teachers have used online evaluation. The purpose of this program is to help teachers prepare learning materials digitally in the form of PDF, PowerPoint and standardized videos. Programs carried out in the form of training to improve teacher skills. The results obtained were an increase in the number of digital learning materials in the form of PPT by 23%, online exam questions by 40%, and learning videos by 18%, all of which were used as digital learning media in E-learning Muhammadiyah (El-Mu).